Determination of some neurotransmitters at cyclodextrin/ionic liquid crystal/graphene composite electrode. (1st May 2016) - Atta, Nada F.; El-Ads, Ekram H.; Ahmed, Yousef M.; Galal, Ahmed
Graphical abstract: Highlights: Glassy carbon is modified with graphene, ionic liquid crystals and cyclodextrin. The modified electrode is used as ultrasensitive sensor for molecules of biological interest. A combined advantage of ionic conductivity, electrocatalysis and surface area is realized. The sensor applicability is demonstrated in urine assays. Abstract: A novel reduced graphene oxide (RGO) composite glassy carbon electrode modified with ionic liquid crystal (ILC), 1-Butyl-1-methylpiperidinium hexa-fluoro-phosphate and cyclodextrin (CD/ILC/RGO/ILC/GC) was fabricated via mechanical casting of each layer. The modified electrode was used for the determination of some neurotransmitters such as dopamine (DA), epinephrine (EP), norepinephrine (NEP), levodopa (L-DOPA), 3, 4-dihydroxy-phenyl acetic acid (DOPAC) and serotonin (ST). This electrode anticipated the good electron mobility and large surface area of graphene, high ionic conductivity and stability of ionic liquid crystal besides the pre-concentrating effect of CD. Optimization of the sensor performance is presented and resulted in a better current signal. The linear dynamic range of the modified electrode was from 0.8×10 −7 –0.1×10 −4  mol L −1 for determination of EP with a correlation coefficient 0.998 and LOD 0.0117×10 −9  mol L −1 . The sensor was sensitive and successfully applied for direct determination of EP in human urine samples with good recovery results.